Sintesis Nanopartikel Seng Oksida (ZnO) dari Limbah Baterai untuk Uji Antimikroba Ekstrak Tanaman Apium graveolens L. terhadap Bakteri Staphylococcus epidermidis - Maulana, Apriyan Bima; Asih, Putri Jeni; Azizah, Salsabila Nur; Aisyah, Aisyah; Aprilliani, Dininur; Lestari, Ajeng Yulianti Dwi (INDONESIAN JOURNAL OF CHEMICAL RESEARCH, 2025)
Battery waste contains hazardous materials that can damage the environment if not properly treated. One innovative solution for managing this waste is the synthesis of zinc oxide (ZnO), known for its strong antimicrobial properties. Additionally, Apium graveolens L. extract is recognized for its significant antibacterial activity. This study aims to synthesize ZnO nanoparticles from battery waste and evaluate their effectiveness in enhancing the antimicrobial activity of Apium graveolens L. extract against Staphylococcus epidermidis. ZnO was synthesized using the coprecipitation method from Zn-C battery waste, and Apium graveolens L. extract was obtained through maceration. The ZnO characterization was conducted using XRD and FTIR, and antimicrobial tests were performed against Staphylococcus epidermidis. The results showed that the synthesized ZnO nanoparticles had an average crystallite size of 41.611 nm with high crystallinity. When combined with Apium graveolens L. extract, the crystallite size became smaller, at 16.881 nm. Antimicrobial tests revealed that ZnO effectively inhibited the growth of S. epidermidis with an inhibition zone of 16 mm, while the combination of ZnO with Apium graveolens L. extract did not show antimicrobial activity. Thus, ZnO synthesized from battery waste is proven to be effective as an antimicrobial agent against S. epidermidis. This synthesis method is also environmentally friendly and has broad application potential.